Exploring Holistic Wellness: Unveiling the Probiotic Wonders of Fermented Dairy – Meet Kefir and Its Health Benefits - Soni, Sushmita; Dangol, Sarbesh Das; Joshi, Jarina (Journal of Nepal Biotechnology Association, 2024)
This article explores the rich historical background and emerging health advantages of kefir, a fermented dairy product renowned for its abundant probiotics and positive impact on gut health and overall well-being. Additionally, the research delves into the microbial composition of kefir, its potential probiotic benefits, and the intricate interplay of microorganisms within the kefir grains. Examining specific Lactobacillus strains, the study assesses their health-promoting benefits, ranging from improved digestion and immune system support to potential contributions to mental health. By scrutinizing the probiotic microorganisms found in kefir, this paper aims to offer valuable insights to researchers, food technologists, and entrepreneurs interested in the nexus of nutrition, health, and sustainable food production.